2005
DOI: 10.1007/s10910-004-6897-4
|View full text |Cite
|
Sign up to set email alerts
|

k-resonance in Toroidal Polyhexes*

Abstract: This paper considers the k-resonance of a toroidal polyhex (or toroidal graphitoid) with a string (p, q, t) of three integers (p ≥ 2, q ≥ 2, 0 ≤ t ≤ p − 1). A toroidal polyhex G is said to be k-resonant if, for 1 ≤ i ≤ k, any i disjoint hexagons are mutually resonant, that is, G has a Kekulé structure (perfect matching) M such that these hexagons are M -alternating (in and off M ). Characterizations for 1, 2 and 3-resonant toroidal polyhexes are given respectively in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A toroidal polyhex H ( p , q , t ) arises from P by identifying the lateral sides, then bottom and top cycles after t torsion (for details, refer to Ref. 31). Hence M 7 can be drawn as H (7,1,3) in Figure 3.…”
Section: Examplesmentioning
confidence: 99%
“…A toroidal polyhex H ( p , q , t ) arises from P by identifying the lateral sides, then bottom and top cycles after t torsion (for details, refer to Ref. 31). Hence M 7 can be drawn as H (7,1,3) in Figure 3.…”
Section: Examplesmentioning
confidence: 99%
“…In particular, he showed that every 3-resonant benzenoid system is also k-resonant (k ≥ 3). This result also holds for coronoid systems [2,18], open-ended nanotubes [29], toroidal polyhexes [25,32] and Klein-bottle polyhexes [26]. For a recent survey on k-resonant benzenoid systems, refer to [13].…”
Section: Introductionmentioning
confidence: 75%
“…In [22], [30], remarkable work have been done in the context of full identification of toroidal fullerenes by employing diversified procedure. Some results about k-resonance of toroidal fullerenes and Kleinbottle polyhex can be found in [31]- [33]. 2-extendability of toroidal and Klein-bottle polyhexes is explained in [34].…”
Section: Graphical Identifications Of Toroidal and Klein-bottle Fmentioning
confidence: 88%